Por que medicina e por que UFSCar: uma resposta - relato de experiência no curso de medicina da Universidade Federal de São Carlos - Torcia, Valeska Cristina (Universidade Federal de São Carlos, 2023)
In this Final Course Work, we are invited to reflect on our experience as students throughout our medical education at the Federal University of São Carlos (UFSCar). The UFSCar Medicine program, aligned with National Curriculum Guidelines, emphasizes the formation of generalist, humanistic, and reflective physicians. Established in 2005 through a partnership between UFSCar and the Municipal Government of São Carlos, the program aims to expand the availability of medical residencies and allocate resources for infrastructure and faculty. My academic journey, initiated with a profound desire to contribute to healthcare, has been both enriching and challenging. Personal experiences, including navigating my father's illness, have strengthened my commitment to the profession. In this work, I underscore the significance of spirituality, psychological support, and adaptation to active teaching methodologies for a more fruitful and balanced experience over the six years of training. The program's alignment with Curriculum Guidelines is reflected in the six-year curriculum, placing a strong emphasis on practical experience from the outset. Participation in internships and complementary activities, such as extension projects, has facilitated exposure to diverse medical fields and professionals, contributing to my personal and professional growth. I highlight the Active Teaching Methodology, centered on students' active participation, as a distinctive feature. Overcoming challenges, the experience stands out for its integration of theory and practice, focus on competencies, and commitment to ethical and humanistic principles. In summary, the journey through UFSCar's Medicine program is characterized by an education aligned with the demands of the medical profession, showcasing continual learning and the resilience to overcome challenges.
Why medicine and why UFSCar: an answer - experience report on the medicine course at the Federal University of São Carlos
Keywords: Metodologias ativas de aprendizagem; Experiência acadêmica; Formação médica; Espiritualidade; Apoio psicológico; Competências médicas; Active learning methodologies; Academic experience; Medical education; Spirituality; Psychological support; Medical competencies; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA